AN ANALYSIS OF ILLOCUTINARY ACT IN DONALD TRUMP’S SPEECH REGARDING COVID-19 - Novan Purwadi; Rissa San Rizqiya (IKIP Siliwangi, 2022)
This research aimed to analyze the categories several illocutionary act that uses by Donald Trumps’ speech, and what is dominant that uses in his speech. This research method is descriptive qualitative and illocutionary act theory by Searle. The data were taken from the CNN News in the Rose Garden of the White House, Friday, May 15, 2020. There were 75 utterances and the percentage of utterances were Assertive53%, Directive 4%, Commissive 14%, Expressive 17%, and Declarative 0%. The result of this research is the dominant that uses by Donald Trumps’ is Assertive 40 utterance, it can be seen that Trump hoped his audiences would be persuaded to act. And based on the result, Donald Trump does not use declarative illocutionary acts in his speech. Keywords: Communication, Speech Act, Illocutionary Act